Application of Probit Analysis to Factors Affecting Small Scale Enterprises' Decision to Take Credit: A Case Study of Oyo State, Nigeria - AJAGBE, F. A (Asian Economic and Financial Review, 2012)
The study assessed the application of porbit analysis to factors affecting small scale enterprises’ decision to take credit: case study of Oyo State, Nigeria. Both questionnaire and interviewed techniques were used for data collection from 35o respondents chosen through stratified sampling techniques. In analyzing the data probit regression was employed in addition to conventional descriptive statistics such as tables, frequency distribution and percentages. The results showed that demand for credit is strongly influenced by gender, age, education, location, value of assets owned and other dwelling characteristics at 1%, 5% and 10% level of significant. The percentage of correct predications which are choice of explanatory variable correctly predicted the household’s demand decisions are good at 70%, 72% and 99% for personal savings, Relatives/ friends and bank. While money lender and multiple sources were insignificant. A comparison of households and enterprise characteristics between those who had used credit and those who had not, as well as between those who used formal sources and those who used informal sources, showed that the differences were not significant in both cases. It is against this background that this recommendation was made that, the credit policy for rural and small-scale lending terms and conditions need to be formulated in order to mobilize savings and maximize the availability of credit to the population in rural and urban areas of Oyo State.